Facile synthesis of a cardanol‐based levelling agent as a biodegradable alternative to tristyrylphenol ethoxylates for the dyeing of polyester fabric. (1st November 2021) - Chen, Kun; He, Jiefang; Tawiah, Benjamin; Zhou, Xiangdong; Zhou, Yuyang
Abstract: To reduce the overdependence on petroleum‐based surfactants for the dyeing of polyester fabrics, a series of biodegradable cardanol‐based polyethoxylate oligomers (CPm, m = 5, 7 and 9) were synthesised by ethoxylation of cardanol with ethylene oxide. The synthesised compounds were characterised and confirmed by Fourier Transform–infrared spectroscopy and proton nuclear magnetic resonance spectroscopy. In addition, the physical, biodegradable and dyeing‐assisting properties of CPm were evaluated through comparison with tristyrylphenol ethoxylates (A typical commercial surfactant). Results revealed that CPm showed a higher hydroxyl value, better dispersing capability and a higher migration percentage than tristyrylphenol ethoxylates. Specifically, CP5 (0.5 g/L) improved the migration percentage by 12.03% compared with tristyrylphenol ethoxylates. The migration performance of the surfactants followed a descending order of CP5 > CP7 > CP9 > tristyrylphenol ethoxylates. Importantly, CP5 displays a higher degradation propensity than tristyrylphenol ethoxylates, demonstrating its biodegradable merit. In summary, the cardanol‐based polyethoxylates synthesised through this research are promising biodegradable and effective alternatives to conventional levelling agents for disperse dyeing, which contributes a new strategy to the sustainable development of the textile industry.